KAMPANYE NILAI-NILAI WASATHIYAH KEPADA MASYARAKAT MELALUI PENGABDIAN SECARA VIRTUAL DI ERA NEW NORMAL - Mega Tunjung Hapsari; Muhamat Rendra Romadon; Septiana Nihayatul Khusna; Zulfiana Suliha Uluwiya; Nicken Impi Eka Sari; Siti Maulidina Azizah (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This community service is carried out by presenting a new concept, namely virtual service from home as an effort to prevent Covid-19 and comply with government recommendations in implementing health protocols. Departing from anxiety and problems related to radicalism, SARA-ism, anarchism, to terrorism, this virtual service activity was carried out in order to campaign wasathiyah values by creating creative content: religious moderation videos, religious moderation posters, quotes, podcasts, and istighotsah (prayer together) virtually through social media Instagram, YouTube and Facebook. This virtual service activity received a very good response from the community, which indicates that this activity was successfully accepted and able to provide benefits to the community in order to foster a sense of unity and respect for differences.